2010
DOI: 10.1007/s12274-010-0038-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and catalytic application of highly ordered mesoporous alumina-carbon nanocomposites

Abstract: Highly ordered mesoporous carbon-alumina nanocomposites (OMCA) have been synthesized for the first time by a multi-component co-assembly method followed by pyrolysis at high temperatures. In this synthesis, resol phenol-formaldehyde resin (PF resin) and alumina sol were respectively used as the carbon and alumina precursors and triblock copolymer Pluronic F127 as the template. N 2 -adsorption measurements, X-ray diffraction, and transmission electron microscopy revealed that, with an increase of the alumina co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…A total TON of Pt for the formation of sorbitol and mannitol was 95 175 in these reactions. In another way, Zhang et al proposed an ordered mesoporous -Al 2 O 3 -C composite for the catalyst support affording both good interaction between Pt and Al 2 O 3 and watertolerant property derived from C. 22 The -Al 2 O 3 phase in the composite was thermally more stable than usual -Al 2 O 3 , but the 100 reusability was not mentioned. A kinetic study of the Pt(N)/BP2000-catalysed reaction indicated that this reaction consists of two steps: the hydrolysis of cellulose to glucose via water-soluble oligosaccharides and the hydrogenation of glucose to sorbitol as expected.…”
Section: Optimisation Of the Catalytic Systemmentioning
confidence: 99%
“…A total TON of Pt for the formation of sorbitol and mannitol was 95 175 in these reactions. In another way, Zhang et al proposed an ordered mesoporous -Al 2 O 3 -C composite for the catalyst support affording both good interaction between Pt and Al 2 O 3 and watertolerant property derived from C. 22 The -Al 2 O 3 phase in the composite was thermally more stable than usual -Al 2 O 3 , but the 100 reusability was not mentioned. A kinetic study of the Pt(N)/BP2000-catalysed reaction indicated that this reaction consists of two steps: the hydrolysis of cellulose to glucose via water-soluble oligosaccharides and the hydrogenation of glucose to sorbitol as expected.…”
Section: Optimisation Of the Catalytic Systemmentioning
confidence: 99%
“…The mesoporous niobia synthesized without resol after calcination are composed of large particles with disordered structures (Figure S3), further suggesting that the resol assistance is crucial for the formation of an ordered Nb 2 O 5 mesostructure. Although previous work shows that mesoporous carbon-TiO 2 , carbon-Al 2 O 3 , and carbon-WO 3 composites [46][47][48] can be synthesized by using resol as the carbon source and block copolymer as the templates, they failed to convert into the corresponding mesoporous metal oxides because of structure collapse during calcination.…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been shown that the addition of inorganic components to the carbon framework suppresses the microporosity of the material. [29] The physical properties of catalysts prepared by impregnation of 15 wt. % Co on different supports are shown in Table 1.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
“…It has been reported that the existence of oxygen-containing functional groups on the carbon support encourages the dispersion and stability of metal catalysts. [33] The 29 Si magic angle spinning (MAS) NMR spectrum of representative mesoporous carbon-silica sample C-Si(28) shows a broad signal at d = À110 ppm, which is attributed to the chemical shift of Q 4 species, indicating the more completely cross-linked framework, [OSiÀO] as shown in Figure 3. These results imply a relatively complex chemical environment around silica, with the possibility of some interaction with the carbon species.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%